Biochar-biodegradable resin composite material for 3D printing and preparation method thereof

By adjusting the particle size and addition amount of biochar and combining the preparation temperature, the problem of low mechanical properties of biodegradable resins in 3D printing is solved, the mechanical properties and thermal stability of composite materials are improved, and the economic and environmental protection of the material is achieved. , expanding its application scope.

CN119119699APending Publication Date: 2024-12-13DALIAN MARITIME UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411423872.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Biodegradable resins have low mechanical properties in applications with high strength demand, and have poor fluidity and narrow melting temperature range during processing, which limits their wide application in the field of 3D printing.

Method used

By adjusting the particle size, addition amount and preparation temperature of biochar, the biochar-biodegradable resin composite material for 3D printing is prepared to improve its mechanics by using the melt blend injection molding method of biochar and biodegradable resin. Characteristics and thermal stability.

Benefits of technology

It significantly improves the mechanical properties and processability of biodegradable resins, reduces material costs, meets green and environmental protection requirements, and accelerates the degradation rate of materials at high temperatures, expanding its application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119699A_ABST
    Figure CN119119699A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of additive manufacturing, in particular to a charcoal-biodegradable resin composite material for 3D printing and a preparation method of the charcoal-biodegradable resin composite material. The composite material is formed by compounding biodegradable resin and biochar through melt blending and injection molding. According to the preparation method, the carbon capturing and collecting capacity of the biochar is fully utilized, the mechanical property, the thermal stability and the crystallization property of the biodegradable resin are regulated and controlled by adjusting the particle size, the adding amount and the preparation temperature of the biochar, and the mechanical property and the machinability of the biodegradable resin are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of additive manufacturing, and in particular, to a biochar-biodegradable resin composite material for 3D printing and a preparation method thereof. Background Art

[0002] Biochar is low-cost, has a wide range of raw materials, and has excellent carbon capture and storage (CCS) capabilities due to its special morphology, thermal stability, and chemical stability. By controlling its preparation temperature, graphite-like molecular domains can be formed, making biochar have great potential in the preparation of green materials.

[0003] Biodegradable resins have obvious advantages in environmental protection and sustainability due to their renewability and good biocompatibility, and are widely used in the automotive industry and 3D printing. However, compared with traditional petrochemical-based plastics, biodegradable resins generally have lower mechanical properties, which limits their use in applications with high strength requirements. Biodegradable resins have problems such as poor fluidity and narrow melting temperature range during processing, which brings certain challenges to production and manufacturing. Therefore, using biochar to strengthen biodegradable resins and prepare degradable bioplastics has broad application prospects and development potential. Summary of the invention

[0004] In order to improve the mechanical properties of biodegradable resin, the present invention provides a biochar-biodegradable resin composite material for 3D printing and a preparation method thereof. The present invention regulates the mechanical properties and thermal stability of the biochar-biodegradable resin composite material by adjusting the particle size, addition amount and preparation temperature of the biochar to meet the actual needs of 3D printing.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] On one hand, the present invention provides a biochar-biodegradable resin composite material for 3D printing, wherein the composite material is compounded by melt blending and injection molding of a biodegradable resin and biochar.

[0007] In the above technical solution, further, the biochar accounts for 1-10% of the mass of the composite material.

[0008] In the above technical solution, further, the biodegradable resin includes one or more combinations of PLA, PGA, PCL, PHB, and PHA.

[0009] Another aspect of the present invention provides a method for preparing the composite material, the method comprising the following steps:

[0010] (1) pyrolyzing the biomass and then crushing it with a planetary ball mill to obtain biochar powder;

[0011] (2) evenly dispersing the biochar powder in a good solvent for a biodegradable resin, stirring, and obtaining a biochar solution, wherein the biochar solution is a homogeneous system without bubbles, aggregates, or biodegradable resin particles;

[0012] (3) adding the biodegradable resin powder to the biochar solution obtained in step (2), stirring, and obtaining a biochar-biodegradable resin mixed solution;

[0013] (4) pouring the biochar-biodegradable resin mixed solution obtained in step (3) into a container, ventilating, and drying after the solvent evaporates;

[0014] (5) The biochar-biodegradable resin composite material dried in step (4) is placed in a pulverizer for pulverization, and the pulverized material is squeezed into wires by a wire extruder to obtain a biochar-biodegradable resin composite material for 3D printing.

[0015] In the above technical solution, further, in step (1), the biomass includes one or more combinations of rice husk, Pinus sylvestris, deciduous leaves, and white pine;

[0016] The biomass is dried before pyrolysis, the drying temperature is 105-110°C, the drying time is 12-24h, the pyrolysis is slow thermal cracking, the pyrolysis is carried out in a tubular furnace, and the pyrolysis temperature is 350-750°C;

[0017] The biochar is dried before ball milling, the drying temperature is 80-90° C., the rotation speed of the planetary ball mill is 200-350 r / min, the crushing time is 0.1-3.5 h, and the particle size of the biochar powder is 0.5-700 μm.

[0018] In the above technical solution, further, in step (2), the good solvent for the biodegradable resin includes one or more combinations of chloroform, dichloromethane, tetrahydrofuran, dimethyl sulfoxide, ethyl acetate, etc.;

[0019] The stirring is carried out by using a stirrer at a rotation speed of 300-500 r / min for 1-2 h.

[0020] In the above technical solution, further, in step (3), the stirring is performed by using a stirrer at a speed of 300-500 r / min for 4-6 hours.

[0021] In the above technical solution, further, in step (4), the ventilation time is 2-3h;

[0022] The drying temperature is 60-80° C., and the drying time is 10-12 hours.

[0023] In the above technical solution, further, in step (5), the crushing time is 5 minutes, intermittent crushing is adopted, and the crushing is stopped for 5 seconds after 10 seconds;

[0024] The wire extruder adopts a two-stage heating and melting method, wherein: the front end melting temperature is 160-190°C, the end extrusion zone temperature is 170-180°C, and the screw speed is 10-20r / min;

[0025] The end of the wire extruder is equipped with a wire traction machine for winding the wire, and the traction speed is 50-70r / min;

[0026] The beneficial effects of the present invention are:

[0027] (1) The present invention fully utilizes the carbon capture and collection capabilities of biochar, and achieves regulation of the mechanical properties, thermal stability and crystallization properties of the biodegradable resin by adjusting the particle size, addition amount and preparation temperature of the biochar, thereby improving the mechanical properties and processability of the biodegradable resin.

[0028] (2) Biochar is a relatively cheap and easily available filler. The present invention can reduce the overall cost while maintaining the material properties by melt blending biochar with a biodegradable resin, making the material more economical, environmentally friendly and sustainable in industrial applications, meeting the requirements of green environmental protection, and helping to reduce the residue and pollution of the material in the environment.

[0029] (3) Biochar reduces the thermal stability of biodegradable resins and can accelerate their degradation rate at higher temperatures, which is very beneficial for application scenarios that require rapid degradation or recycling. It helps to reduce the impact of plastic waste on the environment and makes it easier to combine with other low-melting-point or easily degradable materials, thereby developing new composite materials and expanding the application areas of biodegradable resins. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The tensile properties test results of the composite materials obtained in Examples 1-7, a is the tensile properties of the composite materials with different PS particle sizes, b is the tensile properties of the composite materials with different PS addition amounts, and c is the composite materials with different PS preparation temperatures;

[0031] Figure 2 The tensile properties test results of the composite material obtained in Example 8;

[0032] Figure 3 This is the TGA analysis of the composite materials prepared in Examples 1, 4 and 5, where a is the TG change, b is the DTG change, and c is the activation energy. DETAILED DESCRIPTION

[0033] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific examples, but the protection scope of the present invention is not limited to the following embodiments.

[0034] The present invention will be further described below in conjunction with embodiments:

[0035] Example 1

[0036] (1) After drying the Scots pine biomass debris in an oven at 105°C for 24 hours, the debris was added to a tube furnace, and the temperature of the tube furnace was adjusted to 550°C. After slow pyrolysis for 60 minutes, Scots pine biochar (PS) was obtained. The cooled PS was dried at 70°C for 10 hours and then transferred to a planetary ball mill. The speed was set to 300 r / min and crushed for 30 minutes to obtain PS powder with a particle size of 7 μm.

[0037] (2) 5 g of PS powder was dried at 70 °C for 10 h and then added to dichloromethane and stirred at 350 r / min for 1.5 h to form a uniform biochar solution;

[0038] (3) drying the PLA powder in an oven at 80° C. for 5 h, adding 95 g of the dried PLA powder to the solution, increasing the stirrer speed to 400 r / min, and stirring for 3 h to obtain a PS-PLA mixed solution;

[0039] (4) pouring the PS-PLA mixed solution obtained in step (3) into an evaporating dish, volatilizing in a fume hood at 24° C. for 6 h, and then drying in an oven at 60° C. for 10 h to obtain a PS-PLA composite material;

[0040] (5) The PS-PLA composite material obtained in step (4) is crushed in a pulverizer. The pulverizing time of the pulverizer is 5 minutes. Intermittent pulverization is adopted. The pulverization is 10 seconds and then stopped for 5 seconds. Then the crushed PS-PLA composite material is placed in an extruder. The temperature of the melting zone is set to 185°C, the temperature of the extrusion zone is set to 180°C, the screw speed is set to 10 r / min, and the speed of the traction machine is set to 60 r / min. The extruded wire is naturally cooled and then bagged.

[0041] In the composite material prepared in Example 1, PS accounts for 5% of the mass of the composite material.

[0042] Example 2

[0043] The preparation method is similar to that of Example 1, except that the pulverization time in step (1) is 10 min and the particle size of the obtained PS powder is 700 μm.

[0044] Example 3

[0045] The preparation method is similar to that of Example 1, except that the pulverization time in step (1) is 200 min and the particle size of the obtained PS powder is 0.5 μm.

[0046] Example 4

[0047] The preparation method is similar to that of Example 1, except that the temperature of the tube furnace in step (1) is 350°C.

[0048] Example 5

[0049] The preparation method is similar to that of Example 1, except that the temperature of the tube furnace in step (1) is 750°C.

[0050] Example 6

[0051] The preparation method is similar to that of Example 1, except that the amount of PS powder added in step (2) is 2.5 g, and the amount of PLA powder added in step (3) is 97.5 g. In the composite material prepared in this example, PS accounts for 2.5% of the mass of the composite material.

[0052] Example 7

[0053] The preparation method is similar to that of Example 1, except that the amount of PS powder added in step (2) is 7.5 g, and the amount of PLA powder added in step (3) is 92.5 g. In the composite material prepared in this example, PS accounts for 7.5% of the mass of the composite material.

[0054] Example 8

[0055] The preparation method is similar to that of Example 1, except that in step (3), PLA powder is replaced by PCL powder.

[0056] The tensile properties of the standard strips printed by adding PS-PLA composite materials with different particle sizes, different addition amounts and different pyrolysis temperatures prepared in Examples 1-7 were measured by the method of national standard GBT1040-2006. The mechanical properties are as follows: Figure 1 As shown in the figure, it can be seen that compared with pure PLA, the tensile properties of the standard sample printed by the PS-PLA composite material are improved by 106%, which shows that the addition of biochar can significantly improve the mechanical properties of PLA, especially the tensile strength, which helps to overcome the inherent brittleness of PLA and expand its use in various applications. Using the same method, the tensile properties of the standard sample printed by the PS-PCL composite material prepared in Example 8 were measured, and the tensile strength was improved by 38% ( Figure 2 ).

[0057] like Figure 3As shown in Figure 2, the weight loss of the PS-PLA composites obtained in Examples 1, 4, and 5 shows a thermal decomposition trend similar to that of PLA as a function of temperature, and all of them are one-step degradation. The initial degradation temperature and maximum decomposition rate temperature of the PS-PLA composites are lower than those of pure PLA. The activation energy required to reach the temperature of the maximum degradation rate is as follows: Figure 3 c. This shows that when the highest degradation temperature is reached, the PS-PLA composite material is more easily degraded. This shows that PS reduces the thermal stability of PLA when the highest degradation temperature is reached, and the degradation process of PS-PLA in the molten state leads to a shortening of the polymer chain length. This also improves the processability of PLA. The effect of PS on the thermal stability of PLA mainly comes from three aspects: (I) Spatial site resistance effect: PLA molecular chains are easily softened when heated, and the presence of PS will hinder the movement of molecular chains, and this hindering effect increases with the increase of PS concentration. (II) Formation of hydrogen bonds: PS forms hydrogen bonds with PLA, hindering the movement of PLA molecular chains. (III) Thermal barrier and thermal conductivity: PS dispersed in PLA will form a thermal barrier, affecting the heat transfer inside the matrix, and then affecting the movement and hydrolysis of the molecular chains.

[0058] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A biochar-biodegradable resin composite material for 3D printing, Features: The composite material is compounded by melt blending and injection molding of biodegradable resin and biochar.

2. The composite material according to claim 1, Features: The biochar accounts for 1-10% of the mass of the composite material.

3. The composite material according to claim 1, Features: The biodegradable resin includes one or more combinations of PLA, PGA, PCL, PHB and PHA.

4. A method for preparing the composite material according to any one of claims 1 to 3, It is characterized in that The method comprises the following steps: (1) pyrolyzing the biomass and then crushing it with a planetary ball mill to obtain biochar powder; (2) uniformly dispersing the biochar powder in a good solvent of a biodegradable resin and stirring to obtain a biochar solution; (3) adding the biodegradable resin powder to the biochar solution obtained in step (2), stirring, and obtaining a biochar-biodegradable resin mixed solution; (4) pouring the biochar-biodegradable resin mixed solution obtained in step (3) into a container, ventilating, and drying after the solvent evaporates; (5) The biochar-biodegradable resin composite material dried in step (4) is placed in a pulverizer for pulverization, and the pulverized material is squeezed into wires by a wire extruder to obtain a biochar-biodegradable resin composite material for 3D printing.

5. The preparation method according to claim 4, It is characterized in that In step (1), the biomass includes one or more of rice husk, Pinus sylvestris, deciduous leaves, and white pine; The pyrolysis is a slow thermal cracking, and the pyrolysis is carried out in a tubular furnace at a pyrolysis temperature of 350-750°C; The rotation speed of the planetary ball mill is 200-350r / min, and the crushing time is 0.1-3.5h; The particle size of the biochar powder is 0.5-700 μm.

6. The preparation method according to claim 4, It is characterized in that In step (2), the good solvent for the biodegradable resin includes one or more combinations of chloroform, dichloromethane, tetrahydrofuran, dimethyl sulfoxide, ethyl acetate, etc.; The stirring is carried out by using a stirrer at a rotation speed of 300-500 r / min for 1-2 h.

7. The preparation method according to claim 4, It is characterized in that In step (3), the stirring is carried out using a stirrer at a speed of 300-500 r / min for 4-6 hours.

8. The preparation method according to claim 4, It is characterized in that In step (4), the drying temperature is 60-80°C and the drying time is 10-12h.

9. The preparation method according to claim 4, It is characterized in that In step (5), the crushing time is 5 minutes, and intermittent crushing is adopted, crushing for 10 seconds and stopping for 5 seconds; The wire extruder adopts a two-stage heating and melting method, wherein: the front end melting temperature is 160-190°C, the end extrusion zone temperature is 170-180°C, and the screw speed is 10-20r / min; The end of the wire extruder is equipped with a wire traction machine for winding the wire, and the traction speed is 50-70r / min.

Citation Information

Cited By

  • Bio-based 3D printing resin composition and preparation method thereof

    CN121736399A